Margaret Dix, Charles Hallpike and the ‘Lagerungs’ Manoeuvre - Péricles Maranhão-Filho; Raj Nandi; Eliana T. Maranhão (Arquivos de Neuro-Psiquiatria)
ABSTRACT The main objective of this manuscript is to describe some personal and professional aspects of two outstanding researchers and pioneers in neuro-otology. Among other achievements, Margaret Ruth Dix, and Charles Skinner Hallpike, designed the most-used provocative test for positional nystagmus for the diagnosis of lithiasis in the vestibular posterior semicircular canal.